Intermittent hypoxic training - should sportsmen really perform it? - Golja, P. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Intermittent hypoxic training (IHT) gained popularity as a method of altitude acclimatisation and thus as potentially beneficial for sports performance. IHT is based on the idea that short, intermittent, intense hypoxic stimuli evoke similar or stronger physiological responses than standard altitude acclimatization, which may in turn prove ergogenic. Extensive validation of IHT is, however, still lacking and was therefore the aim of the present study. Fourteen healthy, well trained, male junior cyclists participated in the study, which was performed in the middle of their competition period. During the course of the study, their training regimen remained unchanged. Seven subjects performed IHT one hour daily, five days per week, for four weeks, and seven acted as controls. During every IHT session, the IHT group inspired a hypoxic gas mixture (FiO2=11.4%; simulated altitude of .4500 m) for seven minutes, which was followed by three minutes of normoxic breathing. The control group did not perform any IHT. The protocol of the study was approved by the Ethics Committee of the Republic of Slovenia. In the IHT group, oxygen saturation (SaO2;%) was measured during every bout and every session of IHT. Haematological parameters (Hb, Htc, erythrocytes, reticulocytes, S-Fe, S-ferritin) were measured at the beginning of the study and after the four weeks. Incremental cycle ergometry at sea level and at simulated altitude of 3000 m (FiO2=13.3%) was performed in a balanced manner by both groups, both, before and after IHT. Oxygen consumption (VO2;ml/min kg), oxygen saturation (SaO2;%), heart rate (HR;bt/min), ventilation (L/min), and ratings of perceived exertion (modified Borg's scale) were measured throughout cycle ergometry. Blood lactate (L;mmol/L) and maximal work load (WLmax;W) were determined at the end of cycling. Multifactorial ANOVA for repeated measures on one factor was used for statistical analysis and the level of p<0.05 was adopted as statistically significant. Six subjects of the IHT and four of the control group completed the study. Incremental cycle ergometry, both, at sea level and at simulated altitude of 3000 m, provided identical results before and after the IHT, in both, IHT and control group. No changes were observed in HR, SaO2, WLmax, VO2max, or ratings of perceived exertion, in neither control nor IHT group. Similarly, haematological parameters remained virtually unchanged in both, control and IHT group, when values obtained prior to and after IHT intervention were compared. The results of the present study suggest that the use of IHT for four weeks does not result in altitude acclimatisation and induces no physiological effects. The current knowledge of molecular responses associated with altitude acclimatisation speaks in favour of the present results. Proposing IHT as an ergogenic method seems highly speculative and should be thoroughly reconsidered.